2019
DOI: 10.3390/geosciences9060271
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Environmental Effects of the 1992 MS7.3 Suusamyr Earthquake, Kyrgyzstan, and Their Implications for Paleo-Earthquake Studies

Abstract: Large pre-historical earthquakes leave traces in the geological and geomorphological record, such as primary and secondary surface ruptures and mass movements, which are the only means to estimate their magnitudes. These environmental earthquake effects (EEEs) can be calibrated using recent seismic events and the Environmental Seismic Intensity Scale (ESI2007). We apply the ESI2007 scale to the 1992 M S 7.3 Suusamyr Earthquake in the Kyrgyz Tien Shan, because similar studies are sparse in that area and geologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…This raises concerns for areas with unconsolidated soil deposits and potential areas for liquefaction or areas having potential for slope failure. Therefore, the compilation and documentation of ground effects emerge as a very useful tool in seismic hazard assessment, particularly in land-use planning for sites for future urban centers or areas with critical life-line facilities [27,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises concerns for areas with unconsolidated soil deposits and potential areas for liquefaction or areas having potential for slope failure. Therefore, the compilation and documentation of ground effects emerge as a very useful tool in seismic hazard assessment, particularly in land-use planning for sites for future urban centers or areas with critical life-line facilities [27,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies have been reported in the literature of estimating the seismic intensity for historical and modern seismic events around the globe [10,16,[21][22][23][24][25][26]. Despite having the upper hand over traditional intensity scales, the ESI-07 scale only has a limited number of entries from Asia or Central Asia [9,25,27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the incorporation of the environmental geological effects into the probabilistic/deterministic hazard analysis appears to be mandatory in order to achieve a more accurate seismic hazard estimation. The paper "Earthquake Environmental Effects of the 1992 M S = 7.3 Suusamyr Earthquake, Kyrgyzstan, and Their Implications for Paleo-Earthquake Studies" by C. Grützner et al [10] presents the application of the ESI-07 scale to the 1992 M S = 7.3 Suusamyr Earthquake in the Kyrgyz Tien Shan. The author shows that the ESI-2007 intensity values distribution differs somewhat from traditional intensity assessments Medvedev-Sponheuer-Karnik (MSK) and Modified Mercalli Intensity scale (MMI), because of the sparse population in the epicentral area and the spatial distribution of primary and secondary Environmental Earthquake Effects (EEEs).…”
mentioning
confidence: 99%
“…Thus, prehistorical events that are not within the scope of any historical archives can be covered. The basic idea of the ESI is to make use of traces of geological and/or geomorphological nature that have been left behind by primary and secondary surface ruptures and mass movements, so generated by large magnitude earthquakes to post-estimate the intensity of the hazard and the magnitude of the event [71]. Example applications of the ESI scale can be found in references [71][72][73][74][75].…”
mentioning
confidence: 99%
“…The basic idea of the ESI is to make use of traces of geological and/or geomorphological nature that have been left behind by primary and secondary surface ruptures and mass movements, so generated by large magnitude earthquakes to post-estimate the intensity of the hazard and the magnitude of the event [71]. Example applications of the ESI scale can be found in references [71][72][73][74][75]. Results reported in reference [73] indicate that incorporating ESI data into probabilistic/deterministic seismic hazard analysis can result in significant changes to the modelled PGA values.…”
mentioning
confidence: 99%